IMPLEMENTATION OF INSTAGRAM DIGITAL MARKETING TOOLS TO IMPROVE SALES OF BUGAR HEALTHY FOOD PRODUCT (The Indonesian Journal of Business Administration, 2019)
Bugar is healthy food product from Bandung. Products from Bugar are fruit salads with variety of fruit, various choices of toppings, and yoghurt as salad dressing. Bugar sales activities are through online media, i.e., Instagram. It is because Instagram has high engagement compared to other social media platforms. But, in terms of sales, Bugar encounters problem, i.e., sales per month did not reach the target. The aim of this study is to find the right marketing strategies to improve sales. The analyses carried out are marketing mix, STP analysis, social media marketing, market analysis, customer analysis, competitor analysis, and trial of Instagram digital marketing tools. The research shows that the implementation of Instagram tools and activities are not successful to improve sales, but it successful to improve awareness. As for sales, the more effective way is to find customers on social media organically combined with customer offline promotions. Solutions that can be offered are increasing customers’ testimonials (E-WOM), maintaining loyal customers, optimizing Instagram Ads, choosing the right selebgrams and food bloggers, and looking for customers organically. To implement it, an action plan that consist of schedule, proposed budget, and estimated results has been created.Keywords: Bugar, Digital Marketing, Fruit Salad, Healthy Food, Instagram